2020
DOI: 10.3340/jkns.2019.0169
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-Stimulating Hormone-Secreting Pituitary Adenomas : Single Institutional Experience of 14 Consecutive Cases

Abstract: Objective : Thyroid-stimulating hormone (TSH)-secreting pituitary adenoma (PA) is an extremely rare functioning form of PA that accounts for 0.7-2% of all such cases. The previously reported outcomes of the surgical removal of TSH-PA are poor. Owing to its extremely low incidence, most available reports on TSH-PA are case reports or small case series. Thus, we investigated the clinical and endocrinological outcomes of surgically treated TSH-PA through our institutional series. Methods : We retrospectively revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Pre-operative management of these patients is vital as perioperative uncontrolled hyperthyroidism can lead to atrial fibrillation [ 32 ]. Pre-operative somatostatin analogues can lead to up to 73% reduction in TSH levels prior to surgery [ 33 ]. Post-operative remission has been noted in up to 70% of cases [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-operative management of these patients is vital as perioperative uncontrolled hyperthyroidism can lead to atrial fibrillation [ 32 ]. Pre-operative somatostatin analogues can lead to up to 73% reduction in TSH levels prior to surgery [ 33 ]. Post-operative remission has been noted in up to 70% of cases [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [20] reported the remission rate as 84%, and similarly Yamada et al [8] reported as 84.4%. In a study by Byun et al [21], the remission rate was reported as 93%, but it's worth noting that only postoperative achievement of a euthyroid state was considered in defining remission. On the other hand, similarly to our study, Azzalin et al [16] reported 66%, and Cossu et al [9] reported pooled remission rate as 66% and 76% after adjuvant radiotherapy and medical therapy respectively, in their systematic review and meta-analysis on TSH PitNET.…”
Section: Discussionmentioning
confidence: 99%
“…Transsphenoidal tumour resection is recommended as the treatment of choice (12) . Joonho Byun et al reported that in 13 of 14 cases of surgical treatment of TSH -oma showed excellent surgical outcomes (19) . In our case, surgical treatment was performed after 4 injections of octreotide analogue with successful TSH normalisation.…”
Section: Discussionmentioning
confidence: 99%